Implementasi Mikhmon dengan Infrastruktur Fiber to the Home Sebagai Internet Service Provider RT RW Net Untuk Sekolah dan Rumah Penduduk - Kusuma, Doni; Suryayusra, Suryayusra; Yadi, Ilman Zuhri; Irawan, Dedi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
With the internet, information that is difficult to information is now only a few moments away. This makes existing communication becomes faster so that the flow of information becomes more accessible to the community. more easily reached by the community. In Muara Merang village, based on the needs of residents and students who need internet network access with the existence of several obstacles, namely areas that have not been covered by network providers and service providers. covered by the provider network and official internet service providers are still quite expensive. expensive. Therefore, building RT RW Net with fiber to the home infrastructure (FTTH) infrastructure, using the FTTH-based RT-RW NET system where according to the survey this system is more durable, effective, and also easy to maintain. Methodology methodology used is Questionnaire. As for some of the tools that must be used are Mikrotik, HTB, 6 FO 2 LAN Switch, Fiber Optic Cable, Patch Cord, Splicer, Spliter. This transmission media has proven to be reliable in the ability to carry data, in this case proven to the user. data, in this case it is evident that the PPPoE user Wifirumahapri gets a speed of 10 Mbps and is in accordance with the results. speed of 10 Mbps and is in accordance with the profile package created on the server on the proxy and Hotspot testing in proxy and Hotspot testing is running well according to the package made in Mikhmon, the results of the The implementation results of the design show that this network infrastructure has succeeded in making a positive contribution to the This network infrastructure has successfully made a positive contribution to increasing internet access at the muara merang village level.